Fracture management for the small animal practitioner - Sylvestre, Anne M. (Anne Madeleine), 1959- (John Wiley & Sons, Inc., 2019)
"Fracture Management for the Small Animal Practitioner offers practical strategies and helpful approaches for managing fractures in dogs and cats. Contains all the information needed to successfully manage the most common fractures in dogs and cats. Emphasizes clinically oriented tips for treating fractures from experienced surgeons. Offers an abundance of color photographs to illustrate the techniques"--Provided by publisher.